Some Identities for Euler and Bernoulli Polynomials and Their Zeros - Taekyun Kim (Axioms, 2018)
In this paper, we study some special polynomials which are related to Euler and Bernoulli polynomials. In addition, we give some identities for these polynomials. Finally, we investigate the zeros of these polynomials by using the computer.